Diagrams of Europeanization: European education governance in the digital age. Issue 6 (1st November 2016) - Decuypere, Mathias
Abstract: European education governance is increasingly affected by and effectuated through digital means. This article presents an analysis of the way in which Europe is increasingly deploying digital technologies, and more specifically websites, in order to shape and communicate its education policies. Drawing on the notion of the diagram as the multimodal combination of texts and visuals into a single plane, the article scrutinizes two websites that play a central role in the production and distribution of policy data: first, the European Commission's Directorate Education and Culture website presenting the Education and Training monitor; second, the Open Education Europa website stimulating the deployment of Open Education practices in Europe. Conceived as active devices, various diagrams on these websites are analyzed in view of the operations they perform. It is argued that these diagrams portray related interplays of absence and presence, enact specific spaces into being, and call for specific ways of taking action upon the reality they purport to represent. As such, diagrams have become an integral part of European education governance in the digital age.